Analisis Pengaruh Budaya Organisasi, Gaya Kepemimpinan Melayani Terhadap Kinerja Pegawai Yang Dimediasi Oleh Kepuasan Kerja (Studi Pada Pegawai Kantor Sinode Gereja Masehi Injili di Minahasa) - Rantung, Ester (JURNAL RISET BISNIS DAN MANAJEMEN, 2015)
Job Performance or achievements of the work is the work that is achieved by a person in performing duties in accordance with the responsibilities assigned to him. Sinode The Christian Evangelical Church In Minahasa(GMIM) office the service center GMIM as the place of the study authors,Where the organizational culture always be assessed in every turn of the head. Many collision on how leaders take a stand against employees or against the other leaders as well as how to serve leader. The results showed servant leadership,job satisfaction and a significant positive effect on employee performance while organizational culture is not a positive and significant influence on employee performance. Keywords: organizational culture,servant leadership. job satisfaction, employee performance